2022
DOI: 10.1007/s40121-022-00713-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax in Children: Hidden Burden and Conspicuous Challenges, a Narrative Review

Abstract: There has been progress towards decreasing malaria prevalence globally; however, Plasmodium vivax has been less responsive to elimination efforts compared with Plasmodium falciparum . P. vivax malaria remains a serious public health concern in regions where it is the dominant species (South and South-East Asia, the Eastern Mediterranean region, and South America) and is increasingly recognized for its contribution to overall morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Second, it can be used for the development of bioreceptors such monoclonal antibodies and aptamers for the diagnosis of P. vivax -specific malaria [ 32 , 55 ]. As mentioned above, since the life cycle of P. vivax in the human host is different that of P. falciparum [ 13 , 14 , 15 , 16 , 17 , 18 ], the parasite must be distinguished. Finally, it can be used as a useful tool for basic research related to identification of the metabolic pathway of parasites involved in PvLDH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it can be used for the development of bioreceptors such monoclonal antibodies and aptamers for the diagnosis of P. vivax -specific malaria [ 32 , 55 ]. As mentioned above, since the life cycle of P. vivax in the human host is different that of P. falciparum [ 13 , 14 , 15 , 16 , 17 , 18 ], the parasite must be distinguished. Finally, it can be used as a useful tool for basic research related to identification of the metabolic pathway of parasites involved in PvLDH.…”
Section: Resultsmentioning
confidence: 99%
“…P. vivax forms a hypnozoite (dormant form) in the liver, which unless completely eliminated, can get re-activated and cause recurrence of malarial infection [ 9 , 10 , 11 , 12 , 13 ]. In addition, recent studies have revealed that P. vivax evades the host immune system [ 14 ], is fatal to infants and children [ 15 ], and invades the reticulocytes (called young red blood cells) [ 16 , 17 , 18 ]. Therefore, measures for eliminating P. vivax are completely warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium vivax is now the predominant malaria parasite species in most of endemic Asia and Latin America. It is an important cause of morbidity and developmental delay in children, and in high transmission settings it contributes to childhood mortality via severe anaemia [45]. The main barrier to P. vivax elimination is relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relapse prevention through adequate 8-aminoquinoline anti-hypnozoite activity must be balanced with the need to avoid clinical haemolysis due to widespread erythrocyte loss associated with G6PD deficiency [ 20 , 22 ]. To minimize risk, the WHO recommends G6PD testing for all individuals before the administration of curative doses of 8-aminoquinolines, where feasible [ 8 , 23 ].…”
Section: Tafenoquine: Key Findings Of Clinical Efficacy and Safetymentioning
confidence: 99%